Smart Office Implementation System for Electrical Energy Consumption Efficiency Using IoT-Based Fuzzy Algorithm - M. Ikhsan U; Andani Achmad; Supriadi Sahibu; Nim Von-Lind (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2025)
Increased electricity consumption in office environments often results in waste and inefficient costs. This study aims to develop an Internet of Things (IoT)-based Smart Office system using a fuzzy algorithm to improve electricity efficiency. The method used is the Research and Development (R&D) approach with the Continuous Improvement Spiral model. This system is designed by utilizing a DHT11 sensor for temperature and an LDR for light intensity, which is connected to an Arduino Nano as the main data processor. Data is processed using a fuzzy algorithm to control electronic devices, such as lights and fans, and monitored through the Blynk application. The results showed that the system was able to reduce electricity consumption from 63.57 kWh to 41.32 kWh, with significant savings in monthly electricity costs. The average sensor accuracy reached 99.40% for DHT11 and 96.36% for LDR. This system makes a positive contribution to energy efficiency and is a sustainable solution for office environments.